Human Dignity as a Keystone of Natural and Positive Law in the Polish Legal System - stasikowski, rafał (Prawo Kanoniczne, 2025)
The aim of the study is to determine the place of human dignity in the legal system. According to Article 30 of the Constitution, the inherent and inalienable dignity of the human person constitutes the foundation of human and civil rights and freedoms. It is inviolable, and its respect and protection are the responsibility of public authorities. The conclusions drawn from this analysis support the view that although natural law does not formally constitute binding law within the Polish system of legal sources, the Constitution declaratively affirms that, beyond the framework of binding positive law, the positivized principle of human dignity is binding as an element of objective natural law. From this principle arise constitutional rights and freedoms, with which the entire legal order of the Republic of Poland must conform. Positive law performs a role similar to the concept of lex humana (i.e., law regulating technical details) in relation to lex naturalis (i.e., law specifying the principles of law) as understood by St. Thomas Aquinas. Provisions of positive law must therefore align with human dignity, which—being a component of natural law—has been positivized within the constitutional system of legal sources. Positive law therefore remains in a permanent substantive connection with natural law, which provides its normative content. Within the constitutional framework, the positivized principle of human dignity functions as a keystone between natural and positive law. It structures positive law in terms of its essential meaning and grants it, when coherent with human dignity, substantive binding force.